Study on the Impact of Climate Warming on Mariculture in China - GAO Jia; YANG Huaiyu (Haiyang Kaifa yu guanli)
The paper aims to reveal the challenges and opportunities faced by mariculture in coastal areas in China under the background of global warming, and to provide a scientific basis for policy making and sustainable development in this field. This paper selects the panel data of 11 coastal provinces (autonomous regions and municipalities) for 35 years (1985-2019) and uses description statistics and panel effect models to deeply explore the trend of regional temperature change and its impact on mariculture yield. The results show that: (1) Although there are inter-annual fluctuations and regional differencesin temperature changes among provinces (autonomous regions and municipalities directly under the Central Government) there is an upward trend on the whole, confirming the macro background of global warming. (2) The overall output of mariculture in China is generally on the rise, especially in Liaoning, Shandong, Fujian, Guangdong and other provinces, which have become the core regions of mariculture in China. (3) Through in-depth analysis of the correlation between the temperature and the mariculture yield, it is found that there is a significant negative relationship between the two, that is, every 1% increase in temperature will lead to a decrease of about 2.65% in the mariculture yield. Further research also reveals that in different marine industrial economic circles, the impact of climate warming on mariculture output is significantly different, which has a certain promoting effect in the Yangtze River Delta economic circle, while it has an obvious inhibitory effect in the Bohai Rim economic circle and the Pearl River Delta economic circle. Based on the above research results, this paper puts forward a series of targeted policy suggestions, including strengthening the construction of climate change research and early warning system, optimize the spatial layout of mariculture industry, strengthen disease prevention and control and health management measures, establish and improve the risk management mechanism, in order to cope with the impact of climate warming, promote the sustained, stable and development of mariculture in China provide important reference.